Dams - Esther Duflo; Rohini Pande (Yale University, Economic Growth Center, 2005)
The construction of large dams is one of the most costly and controversial forms of public infrastructure investment in developing countries, but little is known about their impact. This paper studies the productivity and distributional effects of large dams in India. To account for endogenous placement of dams we use GIS data and the fact that river gradient affects a district's suitability for dams to provide instrumental variable estimates of their impact. We find that, in a district where a dam is built, agricultural production does not increase but poverty does. In contrast, districts located downstream from the dam benefit from increased irrigation and see agricultural production increase and poverty fall. Overall, our estimates suggest that large dam construction in India is a marginally cost-effective investment with significant distributional implications, and has, in aggregate, increased poverty.
Keywords: O21; O12; H43; H23; 330; Dams; Development Planning; Program Evaluation; India; Talsperre; Produktivität; Armut; Indien; Verteilungswirkung